2011
DOI: 10.1126/science.1196164
|View full text |Cite
|
Sign up to set email alerts
|

Early Tagging of Cortical Networks Is Required for the Formation of Enduring Associative Memory

Abstract: Although formation and stabilization of long-lasting associative memories are thought to require time-dependent coordinated hippocampal-cortical interactions, the underlying mechanisms remain unclear. Here, we present evidence that neurons in the rat cortex must undergo a "tagging process" upon encoding to ensure the progressive hippocampal-driven rewiring of cortical networks that support remote memory storage. This process was AMPA- and N-methyl-D-aspartate receptor-dependent, information-specific, and capab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

38
305
2
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 323 publications
(360 citation statements)
references
References 28 publications
38
305
2
3
Order By: Relevance
“…The data also show that these marks occur at the zif268 promoter and correlate with a shift of zif268 expression from the hippocampus to the PFC as the memory matures, suggesting an important functional role of these histone PTMs in memory consolidation. The results are in line with several recent findings showing that enhancing histone acetylation favours memory, including object 13,31 , fear 10,12,14,15,17,[32][33][34] , spatial 13,34 and taste 19,35 memory. They significantly extend these findings by showing that in addition to histone acetylation, histone phosphorylation and methylation (on H3K36) are activated in a temporally and spatially regulated manner during memory consolidation in both the hippocampus and the cortex.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The data also show that these marks occur at the zif268 promoter and correlate with a shift of zif268 expression from the hippocampus to the PFC as the memory matures, suggesting an important functional role of these histone PTMs in memory consolidation. The results are in line with several recent findings showing that enhancing histone acetylation favours memory, including object 13,31 , fear 10,12,14,15,17,[32][33][34] , spatial 13,34 and taste 19,35 memory. They significantly extend these findings by showing that in addition to histone acetylation, histone phosphorylation and methylation (on H3K36) are activated in a temporally and spatially regulated manner during memory consolidation in both the hippocampus and the cortex.…”
Section: Discussionsupporting
confidence: 92%
“…We focused on PTMs previously associated with the formation of longterm associative memory 10,[12][13][14][15]19 , specifically phosphorylation of S10, acetylation of K14 and trimethylation of K36 on histone 3 (H3), and acetylation of K5 on H4. As the formation and storage of object memory depend on a temporally regulated interplay between hippocampal and cortical areas, in particular the PFC 20,21 , we postulated that PTMs occur in both brain regions but may be differentially regulated over time.…”
Section: Hippocampal Histone Ptms Are Induced Rapidly But Transientlymentioning
confidence: 99%
“…Spine remodeling and growth has been shown to occur in superficial layers during remote memory formation in mice (Lesburguères et al 2011;Vetere et al 2011;Xie et al 2014), and contextual fear conditioning has been shown to determine a memory-related activation of sparse neurons in layer II of several cortices in mice, which lasts for 2 months (Xie et al 2014). Taken together, past and the present data support the view that superficial layers represent key sites for memory processes.…”
Section: Layer-specific Memory Evoked Activity In the Te2 Cortexsupporting
confidence: 78%
“…Further studies confirmed the recruitment of layer II/III interneurons in auditory fear memory in mice (Pi et al 2013;Sarro et al 2015) Changes in neuronal activity have also been detected in superficial layers during spatial (Maviel et al 2004) and other hippocampal-dependent (Frankland et al 2004;Lesburguères et al 2011) tasks in both rats and mice brain cortices, including the prefrontal, anterior cingulate, parietal and temporal cortices (Frankland and Bontempi 2005). Spine remodeling and growth has been shown to occur in superficial layers during remote memory formation in mice (Lesburguères et al 2011;Vetere et al 2011;Xie et al 2014), and contextual fear conditioning has been shown to determine a memory-related activation of sparse neurons in layer II of several cortices in mice, which lasts for 2 months (Xie et al 2014).…”
Section: Layer-specific Memory Evoked Activity In the Te2 Cortexmentioning
confidence: 62%
“…However, when recently encoded information interacts with an already stored associative schema, systems-level consolidation may well be very rapid (Tse et al 2007(Tse et al , 2011. Consistent with the standard model of memory consolidation, it has been shown that, while the hippocampus is mainly involved in consolidating and recalling recent episodic-like memories, some cortical regions, including prelimbic, orbitofrontal, and anterior cingulate areas, are involved preferentially with remote, well-consolidated memory traces (Frankland et al 2004;Maviel et al 2004;Shan et al 2008;Lesburgueres et al 2011;Tse et al 2011).The retrosplenial cortex (RSC) comprises the entire posterior cingulate cortex in rodents (Vogt and Peters 1981) and is one of the largest cortical areas in the rat. Situated at the crossroads between the hippocampal formation and many neocortical areas, it has attracted much attention especially for its involvement in cognition (Vann et al 2009).…”
mentioning
confidence: 66%